Inventor of the future : the visionary life of Buckminster Fuller - Nevala-Lee, Alec (Dey St., an imprint of William Morrow, 2022)
"From Alec Nevala-Lee, the author of the Hugo and Locus Award finalist Astounding, comes a revelatory biography of the visionary designer who defined the rules of startup culture and shaped America's idea of the future. During his lifetime, Buckminster Fuller was hailed as one of the greatest geniuses of the twentieth century. As the architectural designer and futurist best known for the geodesic dome, he enthralled a vast popular audience, inspired devotion from both the counterculture and the establishment, and was praised as a modern Leonardo da Vinci. To his admirers, he exemplified what one man could accomplish by approaching urgent design problems using a radically unconventional set of strategies, which he based on a mystical conception of the universe's geometry. His views on sustainability, as embodied in the image of Spaceship Earth, convinced him that it was possible to provide for all humanity through the efficient use of planetary resources. From Epcot Center to the molecule named in his honor as the buckyball, Fuller's legacy endures to this day, and his belief in the transformative potential of technology profoundly influenced the founders of Silicon Valley. Inventor of the Future is the first authoritative biography to cover all aspects of Fuller's career. Drawing on meticulous research, dozens of interviews, and thousands of unpublished documents, Nevala-Lee has produced a riveting portrait that transcends the myth of Fuller as an otherworldly generalist. It reconstructs the true origins of his most famous inventions, including the Dymaxion Car, the Wichita House, and the dome itself; his fraught relationships with his students and collaborators; his interactions with Frank Lloyd Wright, Isamu Noguchi, Clare Boothe Luce, John Cage, Steve Jobs, and many others; and his tumultuous private life, in which his determination to succeed on his own terms came at an immense personal cost. In an era of accelerating change, Fuller's example remains enormously relevant, and his lessons for designers, activists, and innovators are as powerful and essential as ever"--